Cataract eye disease in dogs: a narrative literature review study (Research, Society and Development, 2025)
The total population of dogs and cats in Brazil is expected to exceed 100 million animals by 2030. Ocular opacity known as cataract is considered the main cause of treatable blindness in dogs, and its classification can vary according to several characteristics, with the degree of progression being the most relevant aspect concerning treatment and subsequent medical procedures. This article aims to present a narrative bibliographic review on cataracts in dogs, exploring the etiopathogenesis, classification, clinical signs, diagnosis, and treatment. Ophthalmology is a prominent field in clinical and surgical practice, both in humans and in veterinary medicine, and there is also a high rate of ocular problems in domestic species. Cataract is a common ocular condition in dogs, which can have several causes, including heredity, diabetes, anterior uveitis, trauma, old age, and congenital anomalies. This study allowed us to understand the dominance and risk factors associated with cataracts in dogs, providing valuable insights for strategies to prevent and manage the disease. Furthermore, evaluating the effectiveness of different therapeutic options is essential to guide veterinarians in choosing the best treatment for each case.